ANALISIS KEPUTUSAN INVESTASI SAHAM DENGAN PENDEKATAN PRICE EARNING RATIO (PER) (Studi Kasus Pada Saham yang termasuk kedalam Jakarta Islamic Index Tahun 2016-2018) - Suwono Suwono; Sartinah Sartinah (AmaNU: Jurnal Manajemen dan Ekonomi, 2021)
This research has the background of many government regulations in the financial sector, especially in the capital market, which causes many investors who want to invest in shares to obtain optimal profits. Therefore, investors need to do a stock valuation first. Stock valuation can be done by investors by analyzing shares through the company's condition, both internally and externally. This is in accordance with the objectives of the research, which is to know the description of the company's financial performance and to know the fairness of the stock price. Knowing the fairness of stock prices can be done through fundamental analysis with the Price Earning Ratio approach. The population in this study are shares included in the Jakarta Islamic Index which were listed on the Indonesia Stock Exchange in 2016-2018. Sampling using a purposive sampling technique and obtained three company shares, namely PT. AKR Corporindo, Tbk, and PT. Unilever Indonesia, Tbk. and PT. United Tractors, Tbk. Data collection techniques using documentation. Data analysis techniques using the PER approach.The results of the study showed that the shares in the three company shares that were used as research samples, namely PT. AKR Corporindo, Tbk. with intrinsic value of Rp.2,996., and PT. Unilever Indonesia, Tbk. with an intrinsic value of Rp.45,366, is in an Overvalued condition, which is intrinsic value is smaller than the market price. The decision that can be taken is to sell shares. While PT. United Tractors, Tbk. with an intrinsic value of Rp.26,293 being in an Undervalued condition, which is an intrinsic value greater than the market price. The decision that can be taken is to buy shares.